Sharing Resources in a Wireless Virtual Network using a Dynamic Algorithm for Allocating Resources - R. Manimegalai (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Since IT permits the establishment of a unique virtual network (VN) on a common physical infrastructure, network virtualization technology research and application have gained popularity in the communication industry in recent years. A proposal has been put out to virtualize wireless networks with the explicit intention of improving the future of the Internet. In order to establish segregation among slices of wireless networks, Bilateral auction-based resource allocation is established., considering that virtual network mapping algorithms are efficient and necessary for the building of virtual networks on the SN using these technologies (VNE). Presently, the consensus among industry experts is that network virtualization technology is a viable remedy for the limited architecture of the Internet. Presently, the consensus among industry experts is that network virtualization technology is a viable remedy for the limited architecture of the Internet. As a result of the scarcity of fundamental technological investigations concerning wireless access network virtualization and the preponderance of current research in this domain being devoted to cable network virtualization, which is predominantly linked to the backbone and network of data centres, wireless network virtualization has become a focal point of academic and industrial research. This initiative aims to expedite the development of wireless skills in order to foster innovation and meet the ever-changing needs of the industry. However, there has been no effort to implement the dynamic resource allocation technique for resource sharing in virtualized wireless networks. Present strategies for allocating resources on local and global virtual networks are examined and summarised in this study. The analysis of the topology properties of physical and virtual networks is conducted using the centrality theory of social and complex networks. Additionally, this study proposes two efficient methods for resource allocation in wireless and cross-domain virtual networks and develops two models for such networks.